PENGARUH EXPERTISE, TRUSTWORTHINESS, LIKABILITY, INFORMATION QUALITY, ENTERTAINMENT VALUE INFLUENCER TERHADAP PURCHASE INTENTION PADA PRODUK MERCHANDISE - Amelia Valentina Hartono; Dewi Mustikasari Immanuel (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
This study aims to determine the effect of Expertise, Trustworthiness, Likability, Information Quality and Entertainment Value on Purchase Intention on merchandise products. To collect research data, 385 questionnaires were distributed to respondents with criteria for women and men with an age range of 18 years to 34 years who are active users of Instagram social media in Indonesia who have seen, followed or are interested in buying products marketed or promoted by influencers. The sampling in this research was done by using purposive sampling method. Where all the questionnaires in this study deserve to be analyzed. In this study, an analysis of the five characteristics of influencers was carried out to determine which characteristics could have an influence on purchase intention. This study analyzes five characteristics which include expertise, trustworthiness, likability, information quality and entertainment value. Where expertise is the knowledge, skills and experience possessed by an influencer, trustworthiness is a trust, honesty, integrity, skills possessed by an influencer, likability refers to the physical appearance, characteristics and personality of the influencer, information quality refers to completeness, clarity and accuracy an information conveyed by influencers and entertainment value which refers to how influencers can provide a personal aesthetic touch that can create entertainment value. This study uses SPSS Multiple Linear Regression analysis where the t-test carried out results in a calculation stating that the characteristics of the influencer, namely expertise (Sig value = 0.034), trustworthiness (Sig value = 0.000), information quality (Sig value = 0.000) and entertainment value. (Sig value = 0.000) has a significant effect on purchase intention because it has a Sig value which is smaller than 0.05. So that the hypothesis in this study, namely H1, H2, H4 and H5 can be accepted. As for the characteristics of the influencer, namely likability (Sig value = 0.287), it has no significant effect because it has a Sig value. which is greater than 0.05. So the hypothesis in this study is H4, rejected